Journal of Palestine studies - Institute for Palestine Studies (Washington, D.C Institute for Palestine Studies, 1997)
The Journal of Palestine Studies is the oldest and most respected English language journal devoted exclusively to Palestinian affairs and the Arab-Israeli conflict. It brings you timely and comprehensive information on the region's political, religious, and cultural concerns. With an emphasis on peaceful resolution of conflict, the journal unites sound research and analysis with a variety of well-informed perspectives by academics, policy makers, and diplomats. Published quarterly, the Journal of Palestine Studies is a vital resource for anyone interested in the Palestine Question.
" A Quarterly on Palestinian affairs and the Arab-Israeli conflict
Keywords: MIDDLE EAST SITUATION; PALESTINE QUESTION; ARAB-ISRAELI CONFLICT; PERIODICALS; Palestine